Interatomic Coulombic electron capture - Gokhberg, Kirill; Cederbaum, Lorenz S. (Physical review. A, Atomic, molecular, and optical physics, 2010)
In a previous publication [K. Gokhberg and L. S. Cederbaum, J. Phys. B 42, 231001 (2009)] we presented the interatomic Coulombic electron capture process—an efficient electron capture mechanism by atoms and ions in the presence of an environment. In the present work we derive and discuss the mechanism in detail. We demonstrate thereby that this mechanism belongs to a family of interatomic electron capture processes driven by electron correlation. In these processes the excess energy released in the capture event is transferred to the environment and used to ionize (or to excite) it. This family includes the processes where the capture is into the lowest or into an excited unoccupied orbital of an atom or ion and proceeds in step with the ionization (or excitation) of the environment, as well as the process where an intermediate autoionizing excited resonance state is formed in the capturing center which subsequently deexcites to a stable state transferring its excess energy to the environment. Detailed derivation of the asymptotic cross sections of these processes is presented. The derived expressions make clear that the environment assisted capture processes can be important for many systems. Illustrative examples are presented for a number of model systems for which the data needed to construct the various capture cross sections are available in the literature.